Low Rates of Blood Transfusion in Elective Resections of Neurofibromas in a Cohort Study: Neurofibroma Length as a Predictor of Transfusion Requirement. Issue 4 (April 2016) - Hivelin, Mikael; Plaud, Benoit; Hemery, Francois; Boulat, Claire; Ortonne, Nicolas; Valleyrie-Allanore, Laurence; Wolkenstein, Pierre; Lantieri, Laurent
Abstract : Background: Neurofibromas in neurofibromatosis type 1 induce aesthetic and functional morbidity. Perioperative bleeding has been reported as an obstacle to neurofibroma resections. The authors studied the requirement for blood transfusion during surgical treatment of neurofibromatosis type 1. Methods: Six hundred twenty-two procedures performed on 390 neurofibromatosis type 1 patients at the national referral center from 1995 to 2011 were analyzed in two chronologic sets of patients: set 1 (February of 1995 to September of 2007), in which only one surgeon operated; and set 2 (October of 2007 to January of 2011), in which two additional surgeons were involved. Malignant peripheral nerve sheath tumors, reconstructive procedures, and spontaneous hemorrhages were excluded from the analysis. Age, sex, preoperative hemoglobin concentration, location, length, estimated volume and histologic features of the largest neurofibroma (cumulative values for multiple neurofibromas), and procedure duration were studied as potential predictors of blood transfusion that were measured in terms of units of packed red blood cells. Results: Seventy reconstructive procedures, two cases of spontaneous hemorrhage, and 32 malignant peripheral nerve sheath tumor resections were excluded. Among 516 procedures (318 and 198 in sets 1 and 2, respectively), 17 (2.7 percent) required blood transfusions. The requirement for transfusion was associated with neurofibroma length in both sets, with an optimal cutoff value of 13 cm in both sets. Conclusions: Contrary to the literature, the requirement for blood transfusion was found to be low (2.7 percent of the cases) during elective resection of neurofibromas in neurofibromatosis type 1. Elective resections of benign neurofibromas less than 13 cm in length were not associated with a requirement for blood transfusion. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III. Abstract : Supplemental Digital Content is available in the text.